Remarks at High-Level Event on Financing for Development in the Era of COVID-19 and Beyond - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, World Bank Group President, spoke at the United Nations high-level event on financing for development in the era of Coronavirus (COVID-19) and Beyond. He spoke about two institutions, the IMF and World Bank working closely together on financial and economic challenges, including and especially those affecting the world’s poor. He highlighted on the announcement of milestone by IMF and World Bank Group that emergency health operations approved and up and running in over hundred developing countries. He described the new support programs that, in following weeks, will help developing countries overcome the pandemic and reclaim focus on growth and sustainable development. He invited the participants of the UN event to join the efforts with additional financing. He strongly welcomed the prompt support of the G20 countries for a suspension of debt service by all official bilateral creditors, which included G20 endorsement for comparable treatment by commercial creditors. He said that the World Bank Group is supporting countries that are participating in the moratorium. He welcomed President Xi Jinping’s recent commitment to China’s full participation in the debt moratorium. He invited commercial creditors to agree on terms of reference to encourage their participation, especially given the focus of the initiative on debt relief for the IDA countries, the world’s poorest. He mentioned that the UN’s call for Multilateral Development Bank debt suspension would be harmful to the world’s poorest countries. He spoke about the recent mischaracterizations by parts of the UN regarding the World Bank Group’s involvement as an observer to Egypt, Ethiopia, and Sudan’s negotiations regarding the Grand Ethiopian Renaissance Dam. He concluded by saying that the World Bank Group now has available COVID-19 financing programs in over one hundred developing countries, and invited use of those pathways to expand the financing of the health emergency and expand the response so that we can meet the full brunt of the crisis in the world’s poorest countries.